Inflammation and anaemia as predictors of cardiovascular mortality in hemodialysis patients - Selim, G; Stojcheva Taneva, O; Ivanovski, N; Zafirovska, K; Sikole, A; Trajcheska, L; Asani, A; Polenakovic, M (Lithografia Antoniadis I - Psarras Th G.P., 2007)
Cardiovascular diseases are the most common causes of death among hemodialysis (HD) patients, yet the risk factors for these events have not been well established. Our study objective was to determine predictors of cardiovascular mortality, considering the non-traditional/disease-related and treatment-related/ cardiovascular risk factor in HD patients.